The use of ultrasonographic measurement of the heart size and fetal heart rate variation for gestational age determination in local Bulgarian goats - Manol Karadaev; Ivan Fasulkov; Nasko Vasilev; Stefka Atanasova (Veterinary Medicine and Science, 2021)
Abstract Background Determination of gestational age in goats was performed using ultrasound measurements of different fetal biometric parameters. There are no data showing quadratic and exponential dependence between fetal heart parameters and gestational age. Objectives The objective of the present study was to test the significance of the defined indicators (fetal heart rate, longitudinal and transverse fetal heart axes) for determining gestational age in local Bulgarian goats. Methods A total of 24 pregnant local Bulgarian goats, aged between 2 and 5 years, body weight 42–50 kg were included in the study. Ultrasonographic examinations were performed weekly on gestational days 21, 28, 35, 42 and 49. After gestational day 49 until parturition, scans were performed biweekly. The data from the measurements were subjected to linear (y = a + bx), quadratic (y = aх2 + bх + c) and exponential (y = axn) correlation. Results: Average fetal heart rate values decreased with pregnancy progression. The coefficient of determination (R2) and standard error of estimate (SEE) of the heart rate indicator were 0.72, 0.75, 0.58 and 15.1, 14.4, 19.2 days, respectively, for the three correlations. Longitudinal diameter (long axis) had the following values for R2 = 0.94, 0.96, 0.96 and for SEE = 7.0, 5.5, 5.5 days, for the linear, quadratic and exponential correlations, respectively, while the values of the fetal heart transverse diameter (short axis) were higher than those of the external one (R2 = 0.95, 0.97, 0.97). Simultaneously, SEE is lower (SEE = 6.1, 4.9, 5.0 days) compared to that found for the long heart fetal axis. Conclusions For precise estimation of gestational age, use of longitudinal (long) and transverse (short) axes is recommended. Fetal heart rate is not an exact indicator but can be used as a reference for gestational age along with changes in the heart size and echogenicity.